SCIENCE-BASED TRANSFORMATION OF TEACHER EDUCATION: TRADITIONAL AND INNOVATIVE BASIS (Konferensiyalar | Conferences, 2024)
This article explores the science-based transformation of teacher education, focusing on both traditional and innovative approaches. It addresses key themes discussed at a conference, including ethnic and cultural factors in modern teacher education, intercultural competence, teacher training and multicultural pedagogy, the technological and digital gap in education, the development of innovative pedagogical technologies, and the formation of foreign language communicative competence. The article highlights the importance of these themes in shaping effective teaching practices and promoting educational equity among culturally diverse learners.